2021
DOI: 10.3390/encyclopedia1030057
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19: Evidenced Health Disparity

Abstract: Health disparity is an unacceptable, unjust, or inequitable difference in health outcomes among different groups of people that affects access to optimal health care, as well as deterring it. Health disparity adversely affects disadvantaged subpopulations due to a higher incidence and prevalence of a particular disease or ill health. Existing health disparity determines whether a disease outbreak such as coronavirus disease 2019, caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), will … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 95 publications
(132 reference statements)
0
2
0
Order By: Relevance
“…Recent vaccination statistics imply a higher social and racial disparity in regions with fewer vaccination rates [20]. To our knowledge, this is the first spatial epidemiological study that investigates the socioeconomic determinants of the COVID-19 vaccination rate in the continental United States.…”
Section: Introductionmentioning
confidence: 95%
“…Recent vaccination statistics imply a higher social and racial disparity in regions with fewer vaccination rates [20]. To our knowledge, this is the first spatial epidemiological study that investigates the socioeconomic determinants of the COVID-19 vaccination rate in the continental United States.…”
Section: Introductionmentioning
confidence: 95%
“…Research showed in 2019 that 55% of global communities, mainly developing countries, had no social protection which exacerbated economic disparities leading to food insecurity, limitations to services, and strain on agriculture economics during COVID [ 2 ]. These strains also contributed to less availability to education and reduced access to health insurance [ 3 ]. By having the highest reported cases of COVID in Southwest Asia and higher confirmed COVID cases and death per capita when compared to other countries in Asia, the Philippines stands out as a developing country recovering from the devastation of COVID [ 4 ].…”
Section: Introductionmentioning
confidence: 99%